دراسة وتحليل تعليمات حوكمة الرقابة الشرعية الصادرة عن بنك الكويت المركزي (Study of the Instructions of Shariah Governance Issued by the Central Bank of Kuwait) - الناهض عبدالعزيز; صوالحي يونس (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص تهدف هذه الدراسة إلى تصحيح المفاهيم الواردة في بعض الدراسات السابقة حول نظام الحوكمة الشرعية لدولة الكويت، خصوصاً التصور الخاطئ لبعض هذه الدراسات حول دور هيئة الفتوى بوزارة الأوقاف والشؤون الإسلامية بدولة الكويت. بالإضافة إلى سعي الدراسة لتوثيق تاريخ تطور تعليمات الحوكمة الشرعية الصادرة عن بنك الكويت المركزي، التي قد أغفلت عنها الدراسات السابقة، من خلال تقسيم تاريخ صدور التعليمات إلى ثلاثة مراحل أساسية. وفي الختام تسعى الدراسة إلى تحليل ودراسة تعليمات "حوكمة الرقابة الشرعية في البنوك الكويتية الإسلامية" الصادرة مؤخراً عن بنك الكويت المركزي، مع بيان آثار هذه التعليمات على البنوك الإسلامية العاملة في دولة الكويت. الكلمات المفتاحيّة: مصرفية إسلامية، حوكمة شرعية، رقابة شرعية، بنك الكويت المركزي. Abstract This study aims at rectifying the concepts contained in some previous studies on the Sharia governance system in the State of Kuwait, especially the misconception of some of these studies on the role of the Fatwa Committee in the Ministry of Awqaf and Islamic Affairs. In addition, the study seeks to document the history of the development of the instructions of the SharÊÑah governance issued by the Central Bank of Kuwait, which has been overlooked by previous studies, by dividing the date of issuing the instructions into three basic stages. Lastly, the study seeks to analyze and study the instructions of the "Governance of SharÊÑah Supervision in Kuwaiti Islamic Banks" issued recently by the Central Bank of Kuwait, with the effect of these instructions on the Islamic banks operating in the State of Kuwait. Keywords: Islamic banking, SharÊÑah governance, SharÊÑah supervision, Central Bank of Kuwait.